Management Assistance in Financial Management Darussalam Dukuhwaluh Boarding School Based Management Information System - Dewi Laela Hilyatin; Akhris Fuadatis Sholihah; Fatimatuzzahro Fatimatuzzahro (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Darussalam Islamic Boarding School as one of the boarding schools whose development is quite rapid is evidenced by the increase in the number of students, supporting facilities and infrastructure, facilities provided, and achievements achieved. Although the achievements obtained are quite good, in terms of data management, pesantren data is still weak, especially pesantren financial data. This service is carried out to assist pesantren in making pesantren database management, especially financial data by building the